Microparticles orchestrating cell fate in bottom-up approaches - Maciel, Marta M. (2022)
The modulation of cells in tissue formation is still one of the hardest tasks to achieve in Tissue Engineering. To control the cell response when undergoing their normal functions such as adhesion, differentiation, assembly, or maturation is vital the development of more successful solutions. Herein, we discuss how microparticles are being overlooked in their potential for controlling the cellular response. Until now, their role was quite often restricted to a reservoir of chemical compounds or as carriers for cell expansion. Nevertheless, microparticles design with the introduction of biophysical and biochemical cues can effectively modulate cell response.